Organoleptic Test for the Addition of Red Sweet Potato, Temulawak, Banana Flower, and Goat Milk in Multi-nutrient Biscuit - Devi Nuraini Santi; Evawany Yunita Aritonang (Journal of Nutrition Science, 2022)
The enrichment of multi-nutrient biscuits, especially by using local ingredients that are proven to have good nutritional values may address the root causes of stunting, such as low socio-economy status and poor knowledge among the people. Moreover, it is a practical solution to reduce the prevalence of stunting. This research employed a quasi-experimental methodology to observe the acceptance of the addition of red sweet potato, temulawak, banana flower, and goat milk in multi-nutrient biscuit. The research population was all children aged between 6 and 7 months old in Langkat. Data analysis carried out was univariate and organoleptic analysis. There were more female toddlers (66.7%) than male. The majority (86.7%) of the research subjects were healthy during data collection and with no history of any diseases in the past one year (73.3%). They had normal birthweight (86.7%) and complete immunization status (53.3%), and were exclusively breastfed (70%) and not stunted (73.3%). There were two types of biscuit, A1 and A2, with different ratio of goat milk prepared in this study. Biscuit A1 with a reduced proportion of goat milk (15 gr) received the highest acceptability test score for color, aroma, texture, and taste.